2013
DOI: 10.3389/fneng.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal number of stimulation contacts for coordinated reset neuromodulation

Abstract: In this computational study we investigate coordinated reset (CR) neuromodulation designed for an effective control of synchronization by multi-site stimulation of neuronal target populations. This method was suggested to effectively counteract pathological neuronal synchrony characteristic for several neurological disorders. We study how many stimulation sites are required for optimal CR-induced desynchronization. We found that a moderate increase of the number of stimulation sites may significantly prolong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 79 publications
(130 reference statements)
0
27
0
Order By: Relevance
“…This is a reason why the effect of ROI width is stronger on global SC than on global SL. 29 It is known from literature that SC has a broader spread of normal values 8 and a lower reproducibility 30,31 than SL. It seems likely that the higher sensitivity on ROI width described in this study is a factor contributing to these characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a reason why the effect of ROI width is stronger on global SC than on global SL. 29 It is known from literature that SC has a broader spread of normal values 8 and a lower reproducibility 30,31 than SL. It seems likely that the higher sensitivity on ROI width described in this study is a factor contributing to these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This length is ROI width dependent in curved ROIs (curvature dependency). 28,29 For example, when the ROI is made wider, the center line of the ROI is shifted outwards. In a curved ROI its length will increase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the average mutual information per unit cost is maximized at a relatively small synchronization level (~30%, Figure 7C) and drops quickly as synchronization level increases. Moreover, this finding may aid in the calibration of the desynchronizing stimulation technique, used in deep brain stimulation for the treatment of the abovementioned diseases [93]. Specifically, it may guide the therapists to perform the desynchronization stimulation such that, instead of shifting the activity of underlying network to a relatively asynchronous state (anti-kindling process) [91,93], push it to a mode with a relatively small synchronization level so that the network's energy efficient state can be provoked.…”
Section: Implications Of Neuronal Synchronization For Energy Efficmentioning
confidence: 96%